PERGESERAN MAKNA, FUNGSI, DAN BENTUK TEMBIKAR TRADISIONAL SUNGAI JANIAH DI TANAH AGAM SUMATRA BARAT - Nuning Y Damayanti (Universitas PGRI Adi Buana Surabaya, 2018)
The background of the establishment of the earthenware craft of Sungai Janiah is acquired from the legend TheSacred Fish, which is a â€œkarmaâ€ of the natureâ€™s authority against a mother who neglected the care of her child, so thatthe child be came a fish. Since then every mother is forbidden to leave her child alone at home. The mother may work athome while taking care of her children. The work chosen is making earthenware, because the easily available rawmaterial, and easily done. The philosophy of the earthenware of Sungai Janiah is â€œMother and Child Philosophyâ€. This isreflected by the attitude and behaviour in making earthenware like child-caring, and each stage of making earthenware isbased on that.The traditional earthenware craft today is decreasingly developing due to its inability to compete with industrial products. The problems most commonly faced are the technological development- and the marketingproblems. This study was done in Sungai Janiah Kabupaten Agam, West Sumatera, because it has never before researchhas been done in this field, and no written reference yet exists concerning this craft. This study had to be done so the nationâ€™s cultural asset will be not forgotten without more and is needed for the scientific world. The method of study used is the qualitative method with the cultural approach. Data of study was acquired by direct observation, and interviews and field notes were made concerning matters that can support the study findings. The study findings can be explained as follow:Commonly the earthenware of Sungai Janiah is round-formed, functioning as household utensils receptacles. The Sungai Janiah earthenware has not experienced many changes in form, but in function and meaning. No changes in form is due to the limited capacity of the craftsmen and the local socio-cultural factor. The change in meaning is due to scientific developments and socio-cultural changes.